Um estudo sobre bases de Schauder em espaços de Banach e aplicações do princípio de seleção de Bessaga-Pelczynski - Pires, Iego Fernandes (2013)
In this work, we will study the basic theory of Schauder basis of Banach spaces. More precisely, we will study the main results involving (unconditionally) Schauder basis, (unconditionally) basic sequences and we will prove an important result of the Banach space theory, the Bessaga- Pelczynski selection principle. We will also study some applications of this principle such that the existence of basic sequences in Banach spaces and the Pitt\'s Theorem for compact operators between sequence spaces.